(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and aim: Frequent fractures are seen with denture bases made of acrylic owing to their poor strength. Also, another vital property of the denture base is the surface roughness as rough surface leads to accumulation of the food particles which further lead to plaque retention. The microorganisms are seen predominantly inhabiting the surface and in this plaque are candida species mainly C. Albicans. The present study was conducted to assess the outcomes of aluminium oxide on surface roughness and flexural strength of heat cure denture base resin. Materials and Methods: The study comprised of two groups of heat cure denture base resin having 15 wt.% aluminium oxide and conventional heat cure denture resin base. For the study, ISO standard size mould was made with brass rectangle investing in the dimensions of 65 mm × 10 mm × 3 mm. 30 specimens were made and were divided into 2 groups of 15 subjects each where Group I was controlling group where no aluminium oxide was added and Group II was experimental with 15 wits% of aluminium oxide. Specimens were then stored for 14 days followed by measurement of flexural strength using 3 points bending test and a profilometer was used to assess the surface roughness. Results: The study results showed that the addition of 15wt% aluminium oxide shows significantly better surface roughness and flexural strength compared to the heat-cured conventional denture base resin.